ANALISIS MANAJEMEN KOPERASI AGRIBISNIS TERHADAP PENINGKATAN PENDAPATAN ANGGOTA KOPERASI HARAPAN INDAH DESA AIR MELES ATAS KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG PROVINSI BENGKULU - Effendi, Darwan; Sari, Venti Novita; Suryani, Rini; Utami, Rizky Septika; Gustian, Meko (Institute of Computer Science (IOCS), 2026)
Agribusiness cooperatives are economic institutions consisting of agribusiness stakeholders whose primary objective is to empower members through collective enterprise management, enhanced market access, and the provision of capital services and agricultural production inputs. In this context, agribusiness cooperative management plays a vital role in strategic decision-making, operational efficiency, and the development of programs aimed at increasing members’ income. Recent studies indicate that the implementation of effective management strategies can improve members’ welfare through holistic and participatory service delivery. In an era of increasingly dynamic economic competition, agribusiness cooperatives face significant challenges in optimizing their institutional functions to generate tangible economic benefits for members. Recent empirical studies demonstrate that effective cooperative management strategies, such as strengthening member participation, sound financial management, and agribusiness development programs, contribute significantly to improvements in members’ income and overall welfare. Moreover, the member-based nature of cooperatives requires democratic governance mechanisms to ensure active member involvement in the decision-making process.